Development and psychometric evaluation of the healthy internet use scale for adolescents. - Özparlak, Arif; Gül, Uğur; Karakaya, Dudu; Efe, Emine (Journal of Pediatric Nursing, 2026)
The aim of this study was to develop the Healthy Internet Use Scale for Adolescents (HIUS-A) and examine its psychometric properties in order to evaluate healthy internet use (HIU) among adolescents. The study was conducted according to a methodological, correlational and cross-sectional design. Data was collected between September and December 2025 at three middle schools and three high schools in the province of Antalya, Türkiye. The study used a stratified sampling method, and it was completed with 516 adolescents. The scale's content validity was examined through expert evaluation, and its construct validity was tested through exploratory and confirmatory factor analyses. The reliability of the scale was assessed using Cronbach's alpha coefficient, split-half reliability, and item-total correlations. The analyses revealed that HIUS-A exhibited a two-factor structure explaining 49.1% of the total variance. These factors were named "self-control" and "conscious use". Confirmatory factor analysis findings revealed that the model showed a good level of fit (χ2/sd = 1.450; RMSEA = 0.042; SRMR = 0.039; CFI = 0.981). The internal consistency coefficient was calculated as 0.864 for the total scale, 0.855 for the "self-control" subscale, and 0.711 for the "conscious use" subscale. HIUS-A is a valid and reliable ten-item assessment tool for evaluating healthy internet use in adolescents. The scale may be used by nurses and other healthcare professionals to determine HIU levels in adolescents and to evaluate the effectiveness of intervention studies relating to HIU. • HIUS-A enables assessment of healthy internet use among adolescents. • HIUS-A showed good validity and reliability in adolescents. • HIUS-A includes 10 items with two subscales: self-control and conscious use.